Antibody‐dependent and antibody‐independent uptake of HBsAg across human leucocyte subsets is similar between individuals with chronic hepatitis B virus infection and healthy donors. Issue 6 (1st February 2017) - Tharinger, H.; Rebbapragada, I.; Samuel, D.; Novikov, N.; Nguyen, M. H.; Jordan, R.; Frey, C. R.; Pflanz, S.
Summary: Maintaining detectable levels of antibodies to hepatitis B surface antigen (HBsAg) in serum after HBsAg sero‐conversion is the key clinical endpoint indicative of recovery from infection with hepatitis B virus (HBV). As HBV‐infected hepatocytes secrete HBsAg subviral particles in vast excess over HBV virions, detectable hepatitis B surface antibody (anti‐HBs) titres imply complete elimination of HBV virions as well as HBsAg particles. Although intrahepatic phagocytes, for example Kupffer cells, are thought to mediate clearance of HBsAg via antibody (Ab)‐dependent and Ab‐independent mechanisms, the relative contributions of circulating phagocytic cell types to HBsAg elimination are poorly characterized. Understanding the role of various immune cell subsets in the clearance of HBsAg is important because Ab‐dependent or Ab‐independent phagocytic HBsAg uptake may modulate presentation of HBsAg‐derived epitopes to antigen‐specific T cells and hence plays a critical role in adaptive immunity against HBV. This study aims to characterize phagocytic leucocyte subsets capable of internalizing HBsAg immune complexes (HBsAg:IC) or un‐complexed HBsAg particles in whole blood directly ex vivo. The data show that uptake of HBsAg:IC occurs most prominently in monocytes, B cells, dendritic cells and in neutrophils. In contrast, B cells, and to a lesser degree also monocytes, seem to be effective phagocytes for un‐complexed HBsAg. Importantly, a similar pattern of phagocytic HBsAg uptake was observed in blood from chronic hepatitis B (CHB) patients compared to healthy controls, suggesting that phagocytosis‐related cellular functions are not altered in the context of CHB.